Electrolytes for the deposition of dark grey / black rhodium / ruthenium alloy layers
By using rhodium and ruthenium compounds in aqueous acidic electrolyte, combined with phosphonic acid and dicarboxylic acid, a rhodium-ruthenium metal layer electrodeposited on a conductive material was successfully prepared, solving the problem of preparing a wear-resistant, crack-free black rhodium-ruthenium layer in the prior art, and achieving cost-effective metal layer preparation.
Patent Information
- Application Number
- CN202080018279.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-08
- Filing Date
- 2020-04-07
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2040-04-07
AI Technical Summary
The prior art is difficult to effectively prepare rhodium-ruthenium metal layers with attractive black tones, wear-resistant and crack-free, especially in the jewelry and consumer goods industries, and are costly.
An aqueous acidic electrolyte containing 0.5 g/l to 15.0 g/l and 0.5 g/l to 10.0 g/l soluble ruthenium compound, combined with phosphonic acid and dicarboxylic acid as inhibitors, is provided for electrodeposition of a rhodium-ruthenium metal layer on a conductive material.
The rhodium-ruthenium metal layer electrodeposited on conductive materials has extremely high wear resistance and attractive dark and neutral tones, and is suitable for contact materials, decorative metal products and jewelry fields.
Smart Images

Figure HDA0003242718370000011 
Figure HDA0003242718370000012 
Figure HDA0003242718370000021
Abstract
Description
[0001] manual
[0002] The invention relates to an electrolyte which allows the electrolytic production of ferrous metal layers consisting of rhodium and ruthenium. A method for producing corresponding articles and the use of the electrolyte are also subject-matter of the invention.
[0003] Consumer and technical articles, pieces of jewellery and decorative items are finished with thin, oxidation-stable metal layers to protect them from corrosion and / or for optical enhancement. These layers must be mechanically stable and should not show any signs of discoloration or wear, even in the case of prolonged use. An efficient way to produce such layers is electroplating methods with which multiple high-quality metal and alloy layers can be obtained. Familiar examples from everyday life are electroplated copper and brass layers on door latches or door handles, chrome coatings on vehicle parts, gold coatings on electroplated tools or watch straps.
[0004] A particular challenge in the field of electroplating finishing is to produce oxidation-stable, electrically conductive and mechanically resilient metal layers in black, which are not only of interest in the decorative and jewelry industry, but can also be used in technical applications, for example in the field of solar technology or as contact materials. Only a few metals can be used to produce oxidation-stable black layers. In addition to ruthenium, rhodium, palladium, chromium and nickel are also suitable. Due to the high costs of the raw materials, the use of the noble metal rhodium is limited to the jewelry industry. Since nickel and nickel-containing metal layers are contact allergens, the use of low-cost nickel and nickel-containing alloys, especially in the jewelry and consumer goods industry, is only possible in exceptional cases and when strict requirements are observed.
[0005] The electrodeposition of black ruthenium layers (black ruthenium) on conductive substrates is the most well known (DE102011115802A1, WO2012171856A2, WO2008226545A1, and the literature cited therein). Black deposits of rhodium (black rhodium) can also be prepared electrolytically (EP171091A2, JP4154988A2, JP61104097A2, JP61084393A2, JP61084392A2; https: / / ep.umicore.com / de / produkte-3 / produktfinder / rhoduna-470-black-rhodium-elektrolyt- / - 470Black).
[0006] Electrodeposition of rhodium-ruthenium metal layers has been described, for example, in DE2429275A and WO2010057573A1. In JPS57101686A, an electrolyte is described with which a metal layer of rhodium and ruthenium can be obtained, which, depending on the conditions, can be dark blue, gray or black. However, the layers prepared with the electrolytes mentioned here do not have the blackness or wear resistance required by the market.
[0007] The aim therefore remains to specify improved metal deposition possibilities that better correspond to the requirements of market participants. In particular, it should be possible to produce metal layers having an attractive black hue, with or without a blue hue, reproducibly in a simple and cost-effective manner. The metal layers obtained should be as crack-free and wear-resistant as possible in order to be able to be used as contact material, decorative metal products and in particular as jewelry pieces. For industrial processes, the deposition should be able to be carried out in a correspondingly efficient manner.
[0008] These and further objects resulting from the prior art in a manner obvious to a person skilled in the art are achieved by the description of an electrolyte according to the features of claim 1. A specific use is set out in claim 3. Claim 8 relates to a method for electrodepositing a metal layer using the electrolyte according to the invention. The corresponding dependent claims relate to preferred embodiments of claims 1, 3 and 8.
[0009] An aqueous acidic electrolyte is provided for producing a dark metal layer on a conductive material, the aqueous acidic electrolyte having:
[0010] - 0.5 g / l to 15.0 g / l of soluble rhodium compounds (relative to the metal);
[0011] - 0.5 g / l to 10.0 g / l of soluble ruthenium compound (relative to the metal);
[0012] - 5 g / l to 150 g / l of acid;
[0013] - phosphonic acids and dicarboxylic acids;
[0014] The stated purpose has been achieved.
[0015] As provided herein, the electrolyte according to the invention allows the electrodeposition of a metal layer on an electrically conductive material, wherein the metal layer has extremely high wear resistance at good electrical conductivity and is therefore intended for use in contact materials. Likewise, the attractive, dark and neutral color tone of the metal layer is also an advantage for use as a decorative element. It is not expected that this can be achieved by the electrolyte provided herein.
[0016] All materials that the person skilled in the art has considered for this purpose are suitable as conductive materials on which the metal layer can be deposited according to the invention. Preferred are those selected from the group consisting of jewelry pieces, bathroom products, metal consumer goods in the kitchen and living area, contact materials such as switches, plug connections, relays and many more.
[0017] The rhodium compound used in the electrolyte according to the invention can be selected by the skilled person in the art. They will make their selection according to the required solubility in the acidic aqueous electrolyte, the deposition capacity associated with the ruthenium compound used and the cost of the rhodium compound.
[0018] In the electrolyte according to the invention, rhodium is present in the form of ions in its dissolved form. It is preferably introduced in the form of a water-soluble salt, which is preferably selected from the group consisting of: pyrophosphates, carbonates, hydroxide carbonates, bicarbonates, sulfites, sulfates, phosphates, nitrites, nitrates, halides, hydroxides, oxide hydroxides, oxides or their combinations. Very particularly preferred is an embodiment in which the metal in the form of an ion salt is optionally used in the group consisting of: pyrophosphates, carbonates, sulfates, hydroxide carbonates, oxide hydroxides, hydroxides and bicarbonates. It is absolutely preferred to use in the electrolyte in the form of a salt of an inorganic acid such as rhodium sulfate or rhodium phosphate. However, in the bath according to the invention, it can also be used as a salt of an organic acid, such as rhodium alkanesulfonate, for example rhodium methanesulfonate or rhodium sulfamic acid, or a mixture of these compounds. The trivalent rhodium compound to be used is also very particularly preferably selected from rhodium(III) fluoride, rhodium(III) chloride, rhodium(III) bromide, rhodium(III) iodide, rhodium(III) oxide hydrate and rhodium(III) sulfate.
[0019] The ruthenium compound to be used in the electrolyte is selected from, for example, ruthenium (III) fluoride, ruthenium (III) chloride, ruthenium (III) bromide, ruthenium (III) iodide, nitrosoruthenium (III) nitrate, ruthenium (III) acetate, ruthenium isocyanide complex, ruthenium nitrilo-hydroxy complex and ruthenium nitrilo-oxalate complex.
[0020] The ruthenium source of the electrolyte according to the present invention is more preferably prepared in situ. Then it contains ruthenium in complex form, preferably as a binuclear complex, which can be obtained in an acidic aqueous solution based on a ruthenium (III) compound, sulfamic acid and / or ammonium sulfamic acid. It is common for each 1g / l of ruthenium to contain an electrolyte bath or a preparation concentrate of 1g / l to 10g / l of aminosulfuric acid and / or ammonium sulfamic acid. For this reason, a mixture containing, for example, a ruthenium (III) compound, sulfamic acid and / or ammonium sulfamic acid is heated for a period of time, thereby forming [Ru2N(H2O)2X8] 3-Salt (X represents a monovalent anion). Ammonium ion, sodium ion or potassium ion can be preferably used as the counter ion (WO2015173186A1 or WO12171856A2 or WO2008116545A1, and related documents cited therein).
[0021] Ruthenium is very particularly preferably in the form of [Ru2N(H2O)2X8] 3- The chlorine complex [Ru2N(H2O)2Cl8] is preferably used in the form of a dinuclear anion nitroamino-halogen complex compound, wherein X is a halide ion such as chlorine, bromine or iodine. In this context, the chlorine complex [Ru2N(H2O)2Cl8] 3- .
[0022] Which metal compound is introduced into the electrolyte in which amount may also depend on the color of the resulting coating and can be adjusted according to customer requirements. As indicated, the metal to be deposited is present in ionically dissolved form in the electrolyte for applying decorative coatings to jewelry articles, consumer goods and technical articles. Rhodium is preferably present in the electrolyte in a concentration of 1 g / l to 10 g / l, more preferably 2 g / l to 7 g / l. The ruthenium concentration is preferably 1 g / l to 8 g / l, more preferably 2 g / l to 6 g / l. The indicated amounts each relate to the amount of metal.
[0023] The electrolyte according to the invention works particularly well in a very acidic pH range. The pH range is specified below. Mineral acids are preferably used to adjust the pH. However, alternatively, organic acids such as sulfonic acids can also be used for this purpose. Particularly preferably, an acid selected from the group consisting of sulfuric acid, hydrochloric acid, methanesulfonic acid, toluenesulfonic acid, benzenesulfonic acid and sulfuric acid is most preferably used.
[0024] The black coloring of the rhodium-ruthenium layer produced by electroplating is achieved by selectively suppressing the deposition rate of the electroplating bath. As inhibitors, and therefore in particular as blackening additives for ruthenium, one or more phosphonic acid derivatives are present in the electrolyte according to the invention. The following compounds are preferably used: aminophosphonic acid (AP), 1-aminomethylphosphonic acid (AMP), aminotris(methylenephosphonic acid) (ATMP), 1-aminoethylphosphonic acid (AEP), 1-aminopropylphosphonic acid (APP), (1-acetylamino-2,2,2-trichloroethyl)phosphonic acid, (1-amino-1-phosphoacetyl)phosphonic acid, (1-benzamido-2,2,2-trichloroethyl)-phosphonic acid, (1-benzamido-2,2-dichlorovinyl)phosphonic acid, (4-chlorophenyl-hydroxymethyl)phosphonic acid, diethylenetriaminepenta(methylene)phosphonic acid. 1-Hydroxyethane-(1,1-diphosphonic acid) (HEDP), hydroxyethyl-amino-bis(methylenephosphonic acid) (HEMPA), hexamethylenediaminetetra(methylenephosphonic acid) (HDTMP), ((hydroxymethylphosphonylmethylamino)methyl)phosphonic acid, nitrilotri(methylenephosphonic acid) (NTMP), 2,2,2-trichloro-1-(furan-2-carbonyl)aminoethylphosphonic acid, salts derived therefrom or condensates derived therefrom, or combinations thereof.
[0025] Particular preference is given to using one or more compounds selected from the group consisting of aminotri(methylenephosphonic acid) (ATMP), diethylenetriaminepenta(methylenephosphonic acid) (DTPMP), ethylenediaminetetra(methylenephosphonic acid) (EDTMP), 1-hydroxyethane-(1,1-diphosphonic acid) (HEDP), hydroxyethyl-amino-di(methylenephosphonic acid) (HEMPA), hexamethylenediaminetetra(methylenephosphonic acid) (HDTMP), salts derived therefrom or condensates derived therefrom, or combinations thereof.
[0026] Aminotri(methylenephosphonic acid) (ATMP), ethylenediaminetetra(methylenephosphonic acid) (EDTMP) and 1-hydroxyethane-(1,1-diphosphonic acid) (HEDP), as well as salts derived therefrom or condensates derived therefrom or combinations thereof are particularly suitable for use in coatings, especially for decorative articles and consumer goods.
[0027] The amount of phosphonic acid can be selected by those skilled in the art. Their decision will be based on the fact that the phosphonic acid shows a sufficient and considerable effect in the sense of the present invention. Phosphonic acid is preferably used in the electrolyte in an amount of 0.5 g / l to 20 g / l. In this context, more preferably 1 g / l to 10 g / l, and most preferably 1 g / l to 5 g / l.
[0028] The dicarboxylic acids used in particular as blackening additives for rhodium deposits are also present in the electrolyte. Suitable for use as dicarboxylic acids are all acids suitable for the above-mentioned purpose by the person skilled in the art, in particular those which are low-cost and fully soluble in aqueous acidic electrolytes. These may be alkyl, alkenyl or aryl dicarboxylic acids, wherein the acidic groups should preferably be able to form internal anhydrides. It can be assumed that the two acidic groups form bidentate complex compounds with the metal to be deposited (in particular rhodium), wherein 5 or 6 rings are formed with the metal atom. Surprisingly, due to the low dissociation of the dicarboxylic acids, the corresponding complexation occurs completely in an acidic environment. However, in the sense of the present invention, this addition exerts a favorable effect on the final metal deposition.
[0029] Very particular preference is given to aromatic dicarboxylic acids which can form 5 or 6 rings with the complexed metal atom and in particular those selected from the group consisting of benzene dicarboxylic acids, naphthol dicarboxylic acids and indenedicarboxylic acids. Particular preference is given to phthalic acid and its salts.
[0030] The amount of the dicarboxylic acid can be selected by a person skilled in the art. Their decision will be based on the fact that the dicarboxylic acid shows a sufficient and still commensurate effect in the sense of the present invention. The dicarboxylic acid is preferably used in an amount of 0.5 g / l to 25 g / l in the electrolyte. In this context, more preferably 1 g / l to 20 g / l, and most preferably 4 g / l to 12 g / l.
[0031] In particular, the electrolyte of the present invention is used to prepare an article having an electrodeposited metal layer, the electrodeposited metal layer comprising metal rhodium and ruthenium in a weight % composition of 40:60 to 90:10 based on the total weight of the two metals, and the metal layer has an L of less than 65 according to the Cielab color system (EN ISO 11664-4, the latest version as of the filing date). * Value and a from -3 to +3 * Value. * The values are advantageously between -7 and +7.
[0032] The Cielab color system uses a three-dimensional color space, where the brightness value L * Orthogonal to the color plane (a * , b * ). * a * b * The most important properties of color models include device independence and perceptual relationships, i.e. colors are defined as those perceived by normal observers under standard light conditions, regardless of how they are generated or reproduced. Color models are defined in EN ISO 11664-4, "Colorimetry - Part 4: CIE 1976L * a * b *Each color in the color space is represented by a Cartesian coordinate {L * ,a * ,b *} color position limit. Based on complementary color theory to build a * b * Coordinate plane. Green and red are located opposite each other in a * On axis; b * The axis extends between blue and yellow. The complementary hues are in each case 180° opposite to each other; gray is at their center (the origin of the coordinates a * =0, b * =0). * The a-axis describes the brightness (luminance) of the color with values from 0 to 100. In this example, this is orthogonal to a * b * It is also called the neutral gray axis because all achromatic colors (gray tones) are contained within the black (L * =0) and white (L * =100). * The axis describes the green or red portion of the color, where negative values represent green and positive values represent red. * The axis describes the blue or yellow portion of the color, with negative values representing blue and positive values representing yellow.
[0033] As described, the electrolyte of the present invention can be used to produce reproducible dark to black layers, possibly with a pronounced blue tint, which best meets the market requirements of the consumer goods and jewelry industries in terms of wear resistance and tint. * It should be noted that the value should not deviate too much from zero in order to achieve different black tones and cool tones. * The values are advantageously between -5 and +5, preferably between -3 and +3 and particularly preferably between -2 and +2. * The value is less than 65, and very preferably less than 60. * The value should be kept as low as possible. * Values, advantageously values between -2 and +2 and very preferably values between -1 and +1 are achieved.
[0034] The composition of the electrodeposited metal layer may vary within the limits of the claims. A person skilled in the art may control the amount, for example, based on the content of the metal in the electrolyte. The decision of a person skilled in the art will be oriented to the intended use of the deposited metal layer. With respect to the metals Rh and Ru, the electrodeposited metal layer preferably has a composition of 55:45 to 90:10, very preferably 70:30 to 80:20.
[0035] The thickness of the metal layer deposited with the electrolyte according to the invention can be determined by a person skilled in the art based on its corresponding required profile. Typically, the thickness will be in the range of 0.5 μm to 1.5 μm, preferably 0.25 μm to 0.75 μm, and very preferably 0.1 μm to 0.5 μm. It should be mentioned that, with the electrolyte according to the invention, correspondingly thick layers can also be electrodeposited without fractures occurring in the metal deposition. This is very surprising, since the brittle rhodium is already prone to such cracking during electrodeposition, given the dark grey / black layer.
[0036] For certain applications, it has proven advantageous to electrolytically apply a thin top layer of black rhodium onto the metal layer deposited with the electrolyte according to the invention. The possibly thicker metal deposit deposited using the electrolyte according to the invention is therefore preferably subsequently used as a sublayer for a further electrodeposited metal layer of rhodium, the latter having a thickness of 0.005 μm to 1 μm, preferably 0.025 μm to 0.75 μm and very preferably 0.05 μm to 0.5 μm. This final black rhodium layer can be achieved with known electrolytes (JP 4154988 A2, JP 61104097 A2, JP 61084393 A2, JP 61084392 A2; https: / / ep.umicore.com / de / produkte-3 / produktfinder / rhoduna-470-black-rhodium-elektrolyt- / - 470Black). Thus, it is extremely surprising that an article with a correspondingly wear-resistant and crack-free even darker metal layer can be obtained more cost-effectively. Therefore, the subject matter of the present invention can also be correspondingly produced with an article having a sublayer deposited according to the invention, which contains the metal rhodium and ruthenium in a weight-% composition of 40:60 to 90:10, based on the sum of the weights of the metal and the electrodeposited top layer, which is preferably only black rhodium. For the above-mentioned layer sequence, the preferred L * The value is less than 50, more preferably less than 47. * The value of is -2 to +3, very preferably 0 to +2, most preferably 0 to +1. * The values of are -1 to +6, very preferably 1.5 to + 4. Mutually, the preferred properties of the sublayers specified above also apply to the layer combinations under consideration here.
[0037] It has been found that the metal deposition discussed herein (both for the Rh / Ru layer and the layer sequence) has a very high wear resistance, which is particularly advantageous both for the jewelry industry and for technical applications (e.g. as contact material). In the so-called Bosch Weinmann test (Bosch-Weinmann, AMErichsen GmbH, publication 317 / DV / 63, or Weinmann K., Farbe und Lack 65 (1959), pages 647-651), using the electrolyte according to the invention, the metal deposition achieves values of less than 2.0 μm / 1000 strokes. More advantageously, even less than 1.0 μm / 1000 strokes can be achieved, and very advantageously less than 0.75 μm / 1000 strokes can be achieved. For such wear-resistant metal depositions, the composition of the rhodium-ruthenium layer is more preferably from 50:50 to 80:20, most preferably from 60:40 to 80:20.
[0038] The subject of the invention is also a method for electrodepositing a metal layer on an electrically conductive material, wherein:
[0039] a) contacting a conductive material as cathode with an aqueous acidic electrolyte according to the invention;
[0040] b) the anode is in contact with an electrolyte; and
[0041] c) Establish sufficient current between the cathode and the anode.
[0042] It should be noted that the embodiments mentioned for the preferred electrolyte and its use also apply mutatis mutandis to the method presented here. During the deposition process, the current density established in the electrolyte between the cathode and the anode can be selected by a person skilled in the art in accordance with the deposition efficiency and quality. Depending on the application and the type of coating equipment, the current density in the electrolyte is advantageously set to 0.1 A / dm 2 Up to 50A / dm 2 If necessary, the current density can be increased or decreased by adjusting system parameters such as coating unit design, flow rate, anode or cathode conditions, etc. 0.2A / dm 2 Up to 25A / dm 2 A current density of 0.25 A / dm is usually favorable, preferably 0.25 A / dm 2 Up to 15A / dm 2 , and particularly preferably 0.25A / dm 2 Up to 10A / dm 2 Most preferably, the current density is 0.5A / dm 2 Up to 6A / dm 2 Inside.
[0043] Typically, thin layer thicknesses in the range of 0.1 μm to 0.3 μm are produced in stenting operations. Therefore, a 0.25 A / dm 2 Up to 5A / dm 2 A further application of low current densities in the drum or vibration technology is when coating contact pins. Here, at 0.25 A / dm 2 Up to 0.75A / dm 2 Layers of approximately 0.25 μm to 0.5 μm thickness are applied in the current density range of 0.1 μm to 1.0 μm. Layer thicknesses in the range of 0.1 μm to 1.0 μm are usually deposited in stent operations, mainly for decorative applications, where the current density is around 0.5 A / dm 2 Up to 5A / dm 2 within the range.
[0044] Instead of direct current, pulsed direct current can also be used. The current is thus interrupted for a certain period of time (pulse plating). In reverse pulse plating, the polarity of the electrode is changed so that partial anodic stripping of the coating occurs. In this way, the layer accumulation is controlled in a continuous alternating manner with cathodic pulses. Using simple pulse conditions, such as a current flow of 1 s at a moderate current density (t on ) and a pulse pause of 0.5s (t off ) results in a uniform coating.
[0045] Suitable substrate materials generally used herein are copper-based materials (such as pure copper, brass or bronze), iron-based materials (such as iron or stainless steel), nickel, gold and silver. The substrate material may also be a multilayer system that has been electroplated or coated with another coating technology. This involves, for example, a circuit board substrate material or an iron material that has been nickel-plated or copper-plated and then optionally gold-plated or pre-silvered. Another substrate material is, for example, a wax core pre-coated with a silver conductive varnish (electroforming).
[0046] As already pointed out, the electrolyte according to the present invention is an acid electrolyte. The pH value should be less than or equal to 2 and should not be lower than 0.2. The pH value is preferably between 0.5 and 1.5. Fluctuations in the pH value of the electrolyte may occur during the electrolysis. In a preferred embodiment of the method of the present invention, the person skilled in the art therefore continues to monitor the pH value during the electrolysis and, if necessary, adjusts it to the nominal value. The acid used in the electrolyte is advantageously used to adjust the pH value.
[0047] The temperature prevailing during the deposition of the rhodium ruthenium metal layer can be selected as desired by the person skilled in the art. Thus, their decision is directed on the one hand to a suitable deposition rate and a suitable current density range and on the other hand to economic aspects or the stability of the electrolyte. It is advantageous to set the temperature to 20° C. to 65° C., preferably 30° C. to 60° C. and particularly preferably 40° C. to 55° C.
[0048] When using the electrolyte according to the invention, it is preferred to use an insoluble anode. Preferred for use as an insoluble anode are those made of a material selected from the group consisting of platinized titanium, graphite, mixed metal oxides, glassy carbon anodes and special carbon materials (DLC, "diamond-like carbon"), or a combination of these anodes. Insoluble anodes of platinized titanium or titanium coated with a mixed metal oxide are advantageous, the mixed metal oxide being preferably selected from iridium oxide, ruthenium oxide, tantalum oxide, and mixtures thereof. Also advantageously used for a specific implementation of the invention are iridium-transition metal oxide-mixed oxide anodes, more preferably mixed oxide anodes consisting of iridium-ruthenium mixed oxides, iridium-ruthenium-titanium mixed oxides or iridium-tantalum mixed oxides. More information can be found in Cobley, AJ et al. (The use of insoluble anodes in acid sulphate copper electrodeposition solutions), Trans IMF, Vol. 79, No. 3, 2001, pp. 113 and 114.
[0049] In order to produce an optimally dark layer, it is advantageous to carry out an anodic post-treatment (see EP 171 091 B1 or https: / / en.wikipedia.org / w / index.php?title=Anodizing&oldid=888700538). This post-treatment, known to the person skilled in the art, can make the rhodium-ruthenium layer or layer sequence mentioned herein even more wear-resistant and darker. Thus, the tendency to form cracks can also be counteracted. For anodization, the article produced according to the invention is introduced into a post-treatment solution and anodized (stainless steel cathode).
[0050] The present invention is further illustrated in the following examples:
[0051] Example 1 :
[0052] The electrolyte according to the invention contains, in addition to 1.5 g / l of rhodium [trirhodium sulfate], 0.5 g / l of ruthenium as [Ru2NCl8(H2O)2] 3- , 4 g / l of ethylenediaminetetrakis(methylenephosphonic acid) (EDTMP) and 11 g / l of potassium hydrogen phthalate as blackening agent in water and 10 g / l of sulfuric acid are used to produce a black, highly conductive and wear-resistant layer on consumer products. The temperature of the electrolyte is 45° C. The pH is about 1.0.
[0053] In the stent coating process, 0.25A / dm 2 Up to 5A / dm 2The resulting layer has very good mechanical stability and is available in a wide range of colors (a * and b * Value) shows black, a very attractive neutral tone.
[0054] The color values are shown in the attached figure ( Figures 1 to 3 ) can be seen in the electrolyte according to the present invention is called RA black.
[0055] Ru 490 and Ru 479 are commercially available black ruthenium electrolytes. 470 and 471 are commercially available black rhodium electrolytes (https: / / ep.umicore.com / en / products / productfinder).
[0056] Example 2
[0057] The electrolyte according to the present invention contains, in addition to 1.0 g / l of rhodium [trirhodium sulfate], 1.0 g / l of ruthenium as [Ru2NCl8(H2O)2] 3- , 5 g / l of ethylenediaminetetrakis(methylenephosphonic acid) (EDTMP) and 7.5 g / l of potassium hydrogen phthalate as blackening agents in water and 10 g / l of sulfuric acid are used to produce a particularly black and wear-resistant layer on consumer products. The temperature of the electrolyte is 45° C. The pH value of the electrolyte is about 1.2.
[0058] In the stent coating process, 0.75A / dm 2 Up to 2A / dm 2 A suitable substrate is pre-coated with a set current density of 1000 N. Then a very deep (L * =47) of black rhodium electrolyte (e.g., 470). This was post-anodically treated at 4 V in a solution containing 10 g / l potassium hydrogen phthalate. The impregnated solution was tempered at 30° C. The resulting layer exhibited a deep black hue and had very good mechanical stability.
Claims
1. An aqueous acidic electrolyte for producing a dark metal layer on a conductive material, the electrolyte comprising: - 0.5 g / l to 15.0 g / l of soluble rhodium compounds, relative to the metal; - 0.5 g / l to 10.0 g / l of soluble ruthenium compounds, relative to the metal; - 5 g / l to 150 g / l of acid; - phosphonic acid and dicarboxylic acid, wherein the phosphonic acid is selected from aminotri(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), ethylenediaminetetra(methylenephosphonic acid), 1-hydroxyethane-(1,1-diphosphonic acid), hydroxyethyl-amino-di(methylenephosphonic acid) and hexamethylenediaminetetra(methylenephosphonic acid), the phosphonic acid being used in the electrolyte in an amount of 1 g / l to 10 g / l; The dicarboxylic acid is selected from benzene dicarboxylic acid, naphthol dicarboxylic acid and indenedicarboxylic acid, and the dicarboxylic acid is used in the electrolyte in an amount of 1 g / l to 20 g / l.
2. The electrolyte according to claim 1, Features Ruthenium is present in the electrolyte as a binuclear complex.
3. Use of the electrolyte according to claim 1 for preparing an article having an electrodeposited metal layer, the electrodeposited metal layer comprising metal rhodium and ruthenium in a weight % composition of 40:60 to 90:10 based on the sum of the weights of the two metals, the metal layer having an L of less than 65 according to the Cielab color system, EN ISO 11664-4, the latest version as of the filing date. * Value and a from -3 to +3 * value.
4. The use according to claim 3, Features The metal layer * Values are between -7 and +7.
5. The use according to claim 3, Features The metal layer serves as an underlayer for a further rhodium electrodeposited metal layer, the latter having a thickness of 0.05 µm to 0.5 µm.
6. The use according to claim 5, Features Layer sequence L * The value is less than 50.
7. The use according to any one of claims 3 to 6, Features The resulting metal layer has a wear resistance of less than 0.75 µm / 1000 strokes in the Bosch-Weinmann test.
8. A method for electrodepositing a metal layer on a conductive material, wherein: a) contacting the conductive material as a cathode with an aqueous acidic electrolyte according to any one of claims 1 or 2; b) an anode in contact with the electrolyte; and c) Establish sufficient current between the cathode and the anode.
9. The method according to claim 8, Features The current density in the electrolyte is 0.1A / dm 2 Up to 50A / dm 2 .
10. The method according to any one of claims 8 or 9, Features The pH value of the electrolyte is between 0.2 and 2.
11. The method according to any one of claims 8 or 9, Features The temperature during electrolysis was between 20°C and 65°C.
12. The method according to any one of claims 8 or 9, Features The deposited metal layer is subjected to an anodic post-treatment.
Citation Information
Patent Citations
Method for corrosion protection treatment of a workpiece made of an aluminum material, in particular an aluminum wrought alloy
DE102011115802A1
Electrolyte FOR THE DEPOSITION OF RHODIUM-RTHENIUM ALLOYS
DE2429275A1
Process for making rhodium-plated article with black color
EP0171091A2
Process for making rhodium-plated article with black color
EP0171091B1
Surface treatment
JP1986084392A